Current overview and potential applications of the soil ecosystem services approach in Brazil - Prado, Rachel Bardy; Fidalgo, Elaine Cristina Cardoso; Monteiro, Joyce Maria Guimarães; Schuler, Azeneth Eufrausino; Vezzani, Fabiane Machado; Garcia, Junior Ruiz; Oliveira, Aline Pacobayba de; Viana, João Herbert Moreira; Pedreira, Bernadete Conceição Carvalho Gomes; Mendes, Ieda de Carvalho; Braga, Adriana Reatto dos Santos; Parron, Lucília Maria; et al. (Pesquisa Agropecuaria Brasileira, 2016)
Human pressure on ecosystems has undesirable impacts on human well-being. After the Millennium Project, much interdisciplinary research has been developed worldwide aiming to understand these impacts on ecosystem flows and processes, and to learn about the costs and the benefits of ecosystem services for production. Soil provides many ecosystem services, since its multi-functionality is the basis for food production, water filtration, nutrient cycling, and other goods essential to life. This article presents the main concepts and classifications of soil ecosystem services and of its functions; the indicators and the methods for assessment, modeling, and valuation of ecosystem services; some recent applications to assess and evaluate impacts of agricultural management practices on soil ecosystem services; as well as challenges and opportunities for research and for development of public policies related to agro-environmental sustainability in Brazil. Although the role of soil in supplying ecosystem services is yet undervalued, scientists are gradually recognizing soil processes and functions as fundamental to assess ecosystem services and the effects of land use and management on them. Interdisciplinary approaches to integrate science and public policies are necessary to build governance based on ecosystem services.